INVESTMENT BEHAVIOR IN THE MILLENNIAL GENERATION IN INDONESIA DURING THE COVID-19 PANDEMIC - Sunarjanto, Nekhasius agus (Fakultas Ekonomi Universitas Wisnuwardhana, 2023)
This research was conducted during a pandemic, the researchers were interested in knowing whether financial distress in the millennial generation in Indonesia was influenced by overconfidence bias, self-attribution bias and confirmation. The sample of this study was 247 respondents using non-probability sampling technique using purposive sampling using SEM (Structural Equation Modeling) analysis technique using the LISREL program. The results of this study show that financial distress is influenced by overconfidence bias, self-attribution bias and confirmation bias. Their investment behavior is not based on good financial literacy so that investing is irrational